Review of the pattern of traumatic limb lesions sustained in cases of hanging. (January 2020) - Mc Cabe, Mark; Fyzul, Noorusamah Nadia; Mulligan, Linda; Curtis, Michael; Cassidy, Marie
Abstract: This retrospective study sought to identify a regular pattern of limb bruising which occurs in association with suicidal or accidental hanging. Following exclusion of cases suspicious for homicide, 82 consecutive cases of hanging from a 10-year period were retrospectively reviewed to identify the pattern of traumatic limb injury in each case. Relevant information such as location, toxicology, and type of suspension was also noted. 72% of the reviewed cases had traumatic limb lesions, the majority of which occurred on the posterior upper limb and the anterior lower limb. Although the distribution of limb injury in our study mirrored that found in the literature, the incidence is much higher than in previous studies (7.4–20%). This could either be due to differences in confounding factors such as intoxication and location of hanging or differences in the practice of recording of limb trauma in hanging between centres. Neither type of suspension nor location of hanging were significantly associated with an increased incidence of traumatic limb injury. Positive toxicology was found to increase the likelihood of sustaining limb injury (p = .044084). In conclusion, the presence of this well documented pattern of traumatic limb lesions in cases of hanging should not always raise suspicion of foul play. Highlights: Traumatic limb lesions occur in a predictable pattern in hanging victims. Positive toxicology increases the risk of traumatic limb lesions in hanging cases. We note a higher incidence of traumatic limb lesions compared with the literature. Abrasions and bruises made up the majority of traumatic limb lesions. Cases in enclosed spaces did not have higher incidence of traumatic limb lesions.